Payment Reform: Analysis of Models and Performance Measurement Implications - Schneider, Eric C. (Rand Health Q, 2011)
Insurers and purchasers of health care in the United States are on the verge of potentially revolutionary changes in the approaches they use to pay for health care. Recently, purchasers and insurers have been experimenting with payment approaches that include incentives to improve quality and reduce the use of unnecessary and costly services. The Patient Protection and Affordable Care Act of 2010 is likely to accelerate payment reform based on performance measurement. This article provides details of the results of a technical report that catalogues nearly 100 implemented and proposed payment reform programs, classifies each of these programs into one of 11 payment reform models, and identifies the performance measurement needs associated with each model. A synthesis of the results suggests near-term priorities for performance measure development and identifies pertinent challenges related to the use of performance measures as a basis for payment reform. The report is also intended to create a shared framework for analysis of future performance measurement opportunities. This report is intended for the many stakeholders tasked with outlining a national quality strategy in the wake of health care reform legislation.